Influence of instrumental activities of daily living on the cognitive impairment: EpiFloripa study. (3rd March 2020) - Ono, Lariane Mortean; Confortin, Susana Cararo; Figueiró, Thamara Hubler; Rech, Cassiano Ricardo; d'Orsi, Eleonora
Abstract: Objective: To investigate the influence of instrumental activities of daily living (IADL) on cognitive impairment of the older adults' population in southern Brazil. Methods: A longitudinal, population-based and home-based study that evaluates the older adults population (60 years or older) living in the city of Florianópolis, Southern Brazil. The sample at the baseline (2009/2010) was composed by 1, 702 older adults. Cognitive impairment and IADL disability were investigated. A multilevel logistic model was used, in which the analyzed variables were included as the first level and time (baseline and follow-up interviews) as the second level variable. Results: The prevalence of cognitive impairment increased from baseline to follow-up. There was an increase in the chance of the older adults presenting cognitive impairment among those with low (OR: 1.5, 95% CI: 1.0–2.3) and moderate/severe disability (OR: 3.2, 95% CI: 2.1–4.9). Adjusted probability of presenting the outcome almost doubled among those with mild disability, and were nearly four times higher among the older adults with moderate/severe disability when compared to those without disability. Conclusions: IADL disability can be considered an indicator of risk for clinical diagnosis of cognitive impairment. Its evaluation and follow-up are of paramount importance, especially in the older adults with mild disability, in order to avoid the progression of functional and cognitive impairment over time.